Issues in determining parenthood in "surrogacy" - Konečná, Hana; Svatoš, Roman (Walter de Gruyter GmbH, 2019)
Surrogacy is a type of medically assisted reproduction (MAR), which is considered to be a relatively simple medical procedure. However, psychosocially, ethically and legally, it is extremely complicated. There has been a significant increase in interest in the procedure lately. This is largely due to the fact that it is now available to groups of applicants other than traditional heterosexual couples of reproductive age. Its purpose is to examine various approaches to determining what is legally acceptable as parenthood after surrogacy. Our conclusion is that the wishes and rights of the individual actors (intended parent(s). surrogate mother, future child, gamete donors and society as a whole) are incompatible and contradictory. None of the probable solutions suggested from different perspectives can ensure that the wishes and rights of all are fulfilled at the same time.
Keywords: surrogacy; medically assisted reproduction; determining parenthood; law; regulation